Clinical characteristics, treatment status and complications in women with tube ovarian abscess and endometriosis: a retrospective study - Hui Li; Yan Zhao; Xiao-hong Chang; Yue Wang; Hong-lan Zhu (BMC, 2021)
Abstract Background The aim of our present study was to investigate the clinical characteristics, treatment status and complications in women with endometriosis (EM) and tube ovarian abscess (TOA) to determine the possible association between TOA and EM. Methods Medical records were used to analyze the clinical characteristics, treatment and complications. Twenty women who were diagnosed with TOA with EM were compared with 93 women diagnosed as having TOA without EM between January, 2008 and December, 2018. Results In this study, TOA patients with EM were significantly more likely to have a lower age range (20-39 years) than the non-EM group [11/20 (55.0%) vs 27/93 (29.0%)]. In addition, TOA patients with EM were associated with a significantly lower rate of parity [11/20 (55.0%) vs 75/93 (80.6%)], higher rates of infertility [8/20(40%) vs 0/93(0%)] and a significantly lower incidence of elevated blood platelet counts [5/20 (25%) vs 43/93 (46.2%)]. Furthermore, women with EM had greater blood loss (347 ± 445.77 vs 204.67 ± 289.46) and an increased complication rate [3/20(15%) vs 0/93(0%)]. Among the 3 patients who had complications in the EM group, 2 patients had septic shock and 1 patient had intestinal obstruction. And 1 case who had septic shock followed by IVF treatment. There was no significance difference on other factors. Conclusions The present study indicated that EM did not increase the difficulty and time of treatment in patients with TOA, but increased bleeding during surgery and serious complications. It is suggested that doctors should pay more attention to postoperative treatment and nursing in women with TOA and EM, especially those who have a history of recent infertility treatment and related procedures.